Tick collection OH4Surveillance 2025 - Anna Omazic (National Veterinary Institute, 2026)
Ticks collected by flagging in northern Sweden. The collection and speciation was financed by the EU funded project OH4Surveillance.
Keywords: Occurrence; OCCURRENCE; Biological Sciences; Biologi